2020
DOI: 10.1007/s00038-020-01373-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing access of HIV and sexual and reproductive health services among adolescent key populations in Kenya

Abstract: Objectives The objective of this study is to identify enablers and barriers in access of HIV and sexual reproductive health (SRH) services among adolescent key populations (KP) in Kenya. Methods A cross-sectional study using qualitative methods was conducted between October 2015 and April 2016. A total of 9 focus group discussions and 18 in-depth interviews were conducted with 108 adolescent KPs in Mombasa, Kisumu and Nairobi Counties of Kenya. Data were recorded digitally, translated, transcribed and coded in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 25 publications
4
47
0
Order By: Relevance
“…These discriminative incidents toward the WSW have also been reported in past research in Tanzania [8]. The WSW behavior is frowned upon by some health care providers, which many cause negative experiences during health care utilization by WSW [8], [10]. Negative experiences may eventually precipitate sub-optimal utilization of services, non-utilization of services, and sometimes self-medication.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…These discriminative incidents toward the WSW have also been reported in past research in Tanzania [8]. The WSW behavior is frowned upon by some health care providers, which many cause negative experiences during health care utilization by WSW [8], [10]. Negative experiences may eventually precipitate sub-optimal utilization of services, non-utilization of services, and sometimes self-medication.…”
Section: Discussionsupporting
confidence: 55%
“…A study in Tanzania indicated stigma, discrimination, shame, mistreatment, and lack of confidentiality as factors for nondisclosure of sexual orientation to health providers by MSM during care, a decision that might have interfered with proper treatment [9]. Similar studies in East Africa and across the world have reported similar barriers to health care access among key population [10], [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In health services, the priority groups often focus on: adolescents [10], mothers and children [11], migrants [12], female sex workers [13] , etc. MSM, as a special population, has been largely ignored by health service projects [9].…”
Section: Introductionmentioning
confidence: 99%